MARKETING STRATEGY AND PROCESSED INNOVATION AS SALES LEVERAGE OF ANOMAN BURNO'S PRODUCTS DURING THE COVID-19 PANDEMIC - Anggia Astuti; Suhari Suhari; Primasari Mahardhika Rahmawati; Musviro Musviro (UNEJ e-Proceeding, 2022)
Introduction: The development of village potential into edutourism has cultural values ​​that must be fulfilled, namely not making changes in the lives of rural communities, people do not go out of their daily routines and highlight local wisdom which is a great potential that can be developed. In Burno village, agronursing-based edutourism is being developed with the Anoman Burno Village School.. The purpose of this community service is to provide training on marketing strategies and processed innovations to increase sales of Anoman Burno products with a decrease in the number of tourists visiting. Methods: Improving the production aspect by combining milk with various spices to increase immunity, improving the marketing aspect by expanding the market that partners can serve online, helping to promote the products produced both online and offline through educational cafes established by partners.Result: The final result of this program is that there is an increase in public knowledge about the use of processed products made from Senduro's typical cow and goat milk together with spices that are commonly found in Burno village as an immune booster during the covid-19 pandemic, improving product quality in terms of feasibility, and attractiveness of superior products. Conclusion: Assistance to partners is very much needed to ensure the achievement of the desired goals from all aspects, so that they can survive, be strong and develop in the midst of competition during the COVID-19 pandemic. Keywords: marketing strategy, processed innovation, leverage, covid-19 pandemic